Exocytosis-coordinated mechanisms for tip growth underlie pollen tube growth guidance. Issue 1 (December 2017) - Luo, Nan; Yan, An; Liu, Gang; Guo, Jingzhe; Rong, Duoyan; Kanaoka, Masahiro; Xiao, Zhen; Xu, Guanshui; Higashiyama, Tetsuya; Cui, Xinping; Yang, Zhenbiao
Abstract Many tip-growing cells are capable of responding to guidance cues, during which cells precisely steer their growth toward the source of guidance signals. Though several players in signal perception have been identified, little is known about the downstream signaling that controls growth direction during guidance. Here, using combined modeling and experimental studies, we demonstrate that the growth guidance ofArabidopsis pollen tubes is regulated by the signaling network that controls tip growth. Tip-localized exocytosis plays a key role in this network by integrating guidance signals with the ROP1 Rho GTPase signaling and coordinating intracellular signaling with cell wall mechanics. This model reproduces the high robustness and responsiveness of pollen tube guidance and explains the connection between guidance efficiency and the parameters of the tip growth system. Hence, our findings establish an exocytosis-coordinated mechanism underlying the cellular pathfinding guided by signal gradients and the mechanistic linkage between tip growth and guidance. Tip-growing cells can find their growing path toward the source of attractive signals. Here, using experimental data and mathematical modeling, Luo et al. demonstrate that tip-localized exocytosis can integrate guidance cues with Rho GTPase signaling to control cell wall mechanics and direct tip growth inArabidopsis pollen tubes.